(untitled) (The Conference Hub, 2025)
This article discusses the theoretical foundations and practical significance of using mobile educational technologies in the process of teaching the subject "Informatics and Information Technologies". The possibilities of developing students’ interest in independent learning and digital competencies using mobile applications, online platforms and digital learning resources are analyzed. The advantages of mobile education, mechanisms for integrating it into the educational process, methodological approaches of teachers and recommendations for increasing efficiency are also given. The results of the study show that mobile educational technologies can enhance interactivity in computer science lessons, individualize the learning process and increase the level of students’ knowledge acquisition.